Экономический анализ и обоснование бизнес-проекта производства инновационных отечественных кормов и кормовых добавок для сельскохозяйственных животных и птицы - Запорожцева, Людмила Анатольевна; Семенов, Сергей Николаевич; Ткачева, Юлия Викторовна (Современная экономика: проблемы и решения, 2023)
Importance: а business project for the production of innovative domestic feed and feed additives from Jerusalem artichoke for farm animals and poultry. Purpose: economic analysis and justification of the feasibility of producing innovative domestic feed and feed additives from Jerusalem artichoke for farm animals and poultry in the Central Federal District. Research design: the feasibility of producing feed additives from Jerusalem artichoke processing waste has been substantiated, since the effect is based on increasing the productivity of cows and the quality of milk; the authors have put forward a hypothesis about maintaining the positive effect in related sectors of livestock farming. An economic analysis of the planned production was carried out through a SWOT analysis of the strengths and weaknesses of the project, threats. As a result of the integral risk assessment, the need to adjust the discount rate was identified, and the overall risk level of the project was assessed by the authors as average. An assessment of the efficiency indicators of business implementation made it possible to establish that the payback period, even taking into account discounting, does not exceed the period of operation of the project of eight years, the profitability of the business in terms of net profit for the entire period exceeds 80%. Results: An economic analysis was carried out and the production of a domestic feed additive from Jerusalem artichoke for feeding farm animals and poultry was justified. The high economic efficiency of its production and sale of feed additives from Jerusalem artichoke waste is associated with the complex economic effect of reducing waste, increasing animal productivity and product quality, and creating jobs. The possibility of scaling the experience of the considered business in the conditions of the Voronezh region and the Central Federal District, where the cultivation of Jerusalem artichoke is widespread, has been proven.